In situ polymerization, thermal, damping, and mechanical properties of multiwalled carbon nanotubes/polyisobutylene‐based polyurethane nanocomposites. Issue 1 (20th February 2014) - Li, Yuqi; Hu, KaiFang; Jiao, Hongyu; Liu, Xiulan; Wang, Qihua; Pan, Guangqin; Zhang, Xinrui; Wang, Tingmei
<x xml:space="preserve">Abstract</x> Despite the development of strong, durable, and cost efficient polyisobutylene‐based polyurethane (PIB‐based PU) materials has yet to be achieved. The well dispersion and maximum interfacial interaction between the nanofiller and the PIB‐based PU at low loading have been scarcely studied. Here, the preparation of PIB‐based PU nanocomposites with Multiwalled carbon nanotubes (MWCNTs) using a simple in situ polymerization method is reported. The thermogravimetric analysis tests show that MWCNTs significantly improved the thermal stability of MWCNTs/PIB‐based PU nanocomposites. Compare to the pure PIB‐based PU the onset temperature of degradation for the nanocomposite was about 20°C higher at 0.7 wt% MWCNTs loading. Efficient load transfer is found between the nanofiller MWCNTs and PIB‐based PU and the mechanical properties of the MWCNTs/PIB‐based PU nanocomposite with well dispersion are improved. A 63% improvement of Young's modulus and slightly increased of tensile strength are achieved by addition of only 0.7 wt% of MWCNTs. The experimentally determined Young's modulus is in well agreement with the theoretical simulation. It is worth noting that the PIB‐based PU and MWCNTs/PIB‐based PU nanocomposites exhibit excellent damping properties (tan δ > 0.3) from −45°C to 8°C. POLYM. COMPOS., 36:198–203, 2015. © 2014 Society of Plastics Engineers